2021
DOI: 10.1097/scs.0000000000008254
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Stability of Alveolar Bone Graft in Cleft Lip and Palate Patients: Systematic Review and Meta-Analysis

Abstract: However, only the lower midfacial area can be advanced, and it is impossible to resolve the overall midface deficiency due to the position of the Le Fort I osteotomy line. 5,9 Thus, facial implant placement can be considered because the upper-midface deficiency cannot be resolved through Le Fort I osteotomy.Various types of prosthesis, including silicone (polydimethylsiloxane), GoreTex (expanded polytetrafluorethylene, WL Gore & Associates Inc, Flagstaff, AZ), and MedPor (high-density porous polyethylene, Pore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 49 publications
0
14
0
1
Order By: Relevance
“…These steps resulted in the inclusion of 18 more SRs. Altogether, 144 SRs and MAs [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , ...…”
Section: Resultsunclassified
See 4 more Smart Citations
“…These steps resulted in the inclusion of 18 more SRs. Altogether, 144 SRs and MAs [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , ...…”
Section: Resultsunclassified
“…There was an increasing trend in their numbers with time. The maximum number of published articles were from the year 2021 (n = 29) [ 28 , 46 , 47 , 48 , 55 , 61 , 62 , 63 , 64 , 65 , 69 , 76 , 81 , 82 , 99 , 100 , 101 , 102 , 111 , 128 , 129 , 130 , 142 , 143 , 145 , 148 , 153 , 154 , 161 ]. It was observed that only three studies performed before 2010 could qualify during the two-stage scrutiny [ 72 , 112 , 113 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations